2020
DOI: 10.1186/s41182-020-00254-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining the knowledge and prevention practice of healthcare workers towards COVID-19 in Amhara region, Ethiopia: a cross-sectional survey

Abstract: Background Healthcare workers (HWs) are at the highest risk of getting CIVID-19. This study aimed to assess factors determining the knowledge and prevention of HWs towards COVID-19 in the Amhara Region, Ethiopia. Methods A cross-sectional online survey was conducted among 442 HWs using email and telegram addresses. The knowledge and practice of HWs were estimated using 16 knowledge and 11 practice questions. A multivariable logistic regression analysis was used on SPSS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

50
164
19
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(253 citation statements)
references
References 34 publications
50
164
19
5
Order By: Relevance
“…This is higher than a study conducted in Ethiopia (62%). 26 The possible reason could be the difference in sample size, way of data collection, and area coverage, but lower than a studies conducted in China (89.7%) 39 and Pakistan (88.7%). 24 This could be due to those studies being conducted in the country where the pandemic was first detected.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…This is higher than a study conducted in Ethiopia (62%). 26 The possible reason could be the difference in sample size, way of data collection, and area coverage, but lower than a studies conducted in China (89.7%) 39 and Pakistan (88.7%). 24 This could be due to those studies being conducted in the country where the pandemic was first detected.…”
Section: Discussionmentioning
confidence: 88%
“…Data were collected by using self-administered questionnaire which was adopted from World Health Organization (WHO), and previous researches, 7,24,26,37,38 with some adjustment. The tool was composed of three parts, ie, Sociodemographic and work related characteristics, perceived barriers related factors, and preventive measures related factors.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…These resulted in the health professionals more vulnerable to the infection and more likely to transmit the disease (COVID-19) to others. Studies conducted in Ethiopia [ 32 ], Pakistan [ 28 ], and China [ 31 ] reported that lack of access to infection prevention training or insufficient/inadequate training in infection control measures resulted in the poor practice of precautionary measures for the COVID-19. A result of systematic review also supplements the findings of the above-stated literature.…”
Section: Discussionmentioning
confidence: 99%
“…Former research findings also supported this where people who have poor knowledge; attitude and practice towards COVID-19 prevention were more affected by COVID-19. 1 This cross-sectional survey is designed to assess the community's level of risk perception of COVID-19, precautionary behavior, and intention to comply with the nonpharmaceutical preventive measures as recommended by the Ethiopian government and WHO at the time of the survey. In addition, the study was designed to capture the community's perception of the effectiveness of precautionary measures recommended, and the effect of media exposure to comply with preventive measures.…”
Section: Introductionmentioning
confidence: 99%